Sexual dimorphism in the brown vine-snake Oxybelis aeneus from the State of Ceara, Brazil - Mesquita, Paulo Cesar Mattos Dourado de (2010)
Several different pressures determine the reproductive success among males and females, and that is the reason why morphological differences between the sexes are expected to be found in any given species. Oxybelis aeneus is a tiny and slender arboreal snake that is widely distributed from the United States to southeastern Brazil. The analysis of 102 specimens provided information on sexual dimorphism for this species. Females are longer and heavier than males, while there is no difference in head size and tail length between males and females.